The wisdom of sheep : observations from a family farm - Young, Rosamund (Penguin Press, 2024)
"A touching, wise and surprising chronicle of the rich inner lives of animals, drawn from Rosamund Young's extraordinary lifetime as an organic farmer We talk a lot about sheep: following the herd, counting sheep to fall asleep and looking out for wolves in sheep's clothing. But, just like people, animals don't always follow the pack. Some are affectionate while others butt heads; some follow the leader while some guide the whole flock home. With startling beauty and tenderness, Rosamund Young reveals the remarkable emotional and intellectual complexity of the animals she lives with on her family farm, and the story of her life's work, with the intimacy of a personal diary. Just as she did in her acclaimed book, The Secret Life of Cows, Young transports readers to the wild meadows of Kite's Nest Farm, where she has worked as an organic farmer for over forty years, at the beck and call of the abundant wildlife, living in direct contact with the consciousnesses of her beloved animals. Through tender portraits of her sometimes eventful but always rewarding days at Kite's Nest, Young recounts a multitude of discoveries, such as how cows converse with one another, why sheep are so strongheaded-and why you should never, ever text whilst milking. That's a lesson you need learn only once. This is a story of joy, discovery, cooperation and, sometimes, heartbreak. But through it all, The Wisdom of Sheep is a fresh and delightful tribute to the miraculous inner worlds of the animals all around us and what we can learn about them, and about ourselves, by watching them more closely"--